Description and distribution of the mechanical papillae of the lingual surface of Antarctic seals species (Phocidae: Carnivora) and their relationship with diet and dental morphology - Loza, Cleopatra Mara; Carlini, Alfredo Armando; Zarza, Renata; Krmpotic, Cecilia Mariana; Galliari, Fernando Carlos; Andrés Laube, Pedro Fernando; Scarano, Alejo Carlos; Parada Gandarilla, Vania; Negrete, Javier; Loureiro, Juan Pablo; Barbeito, Claudio Gustavo (Polar Biology)
The tongue is a solid muscular organ belonging to the first portion of the digestive system. Its dorsal surface is characterized by the presence of mechanical papillae and taste buds. Mechanical papillae have been classified according to their morphology (i.e., filiform, conical, lenticular and marginal), and its type, shape, relative quantity and distribution have been linked to different eating habits. In this contribution, we analyze the dorsal surface of the southern Antarctic seals’ tongues Mirounga leonina, Leptonychotes weddellii, Lobodon carcinophaga and Hydrurga leptonyx. We evaluate the distribution, quantity, morphology, and density of mechanical lingual papillae in the context of eating habits preferences of each species, and food items included in their diet. The complexity in the topography of the lingual surfaces correlates with the complexity of the crowns of the postcanine teeth. In M. leonina, the lingual surface is smooth, with small crowns without cusps; L. weddellii has some papillae on the body and some postcanines with small cusps; H. leptonyx has a large number of papillae, and the crowns are complex with several cusps; and L. carcinophaga has the greatest abundance and distribution of filiform papillae and the maximum development in complexity of the postcanine crowns. Finally, we show our results in relation to the phylogenetic groupings resulting from analyzing the evolution of prey capture techniques in pinnipedimorphs and the dental morphology, and conclude that our results match with that proposed phylogeny. Fil: Loza, Cleopatra Mara. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Morfología Evolutiva y Desarrollo; Argentina Fil: Carlini, Alfredo Armando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de ...